Partial purification and characterization of an inactive precursor of Pseudomonas aeruginosa elastase. - Kessler, E (1988)
An inactive precursor of the extracellular elastase of Pseudomonas aeruginosa was extensively purified by immunoadsorption chromatography of the soluble bacterial cell fraction on a column of Sepharose coupled to antielastase antibodies. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the purified precursor fraction revealed two major protein bands with molecular weights of about 36,000 (P36) and 20,000 (P20) that in the absence of sodium dodecyl sulfate were associated with each other. The following findings identify P36 as the elastase precursor and indicate that proteolytic processing of this molecule is required for activation: (i) P36 is larger than the elastase, and it binds antielastase antibodies; (ii) trypsin activation is associated with the disappearance of P36 and the appearance of a new protein band migrating identically with the elastase and reacting with antibodies against the elastase; (iii) peptide maps generated from P36 and the elastase are similar although not identical. P20 by itself was not recognized by antielastase antibodies. Its association with P36 accounts for its adsorption to the immunoaffinity column and suggests that it may serve in elastase secretion.